THE EFFECT OF FINANCIAL BEHAVIOR, FINANCIAL LITERACY AND DEMOGRAPHIC FACTOR ON STUDENTS' INVESTMENT DECISION MAKING - Normalasari Normalasari; Maslichah Maslichah; Dwiyani Sudaryanti (Universitas Islam Malang, 2022)
Background. Financial behavior, financial literacy, and demographic factors affect investors' investment decision-making. Investment activities need a plan to make investors more confident in making investment decisions.Purpose. This kind of study is a correlational study that aims to determine the effect of Financial Behavior, Financial Literacy, and Ethnic and to know the extent of the impact of dependent variables on students' investment decision making.Method. In this study, the sample was determined by purposive sampling with certain criteria, namely active students of the Faculty of Economics and Business, University of Islam Malang, Brawijaya University, and Malang State University, had taken Financial Market and Capital Market courses or similar courses and had invested when they were a student. The number of samples was 96, which were analyzed by SPSS.Results. This study shows that Financial Behavior and Financial Literacy have a significant positive effect on students' investment decision-making while Ethnic as Demographic Factor has no significant effect on students' investment decision-making.Keywords: Financial Behavior, Financial Literacy, Demographic Factor, Students' Investment Decision Making